1996
DOI: 10.1029/95jc03015
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of surface wind products over the North Pacific Ocean

Abstract: This study compares four surface wind products Which may be used to force ocean circulation models of the North Pacific: wind stress derived from the Atlas special sensor microwave imager (SSM/I) based surface wind analyses (July 1987-June 1990), the Goddard Earth Observing System (GEOS) wind assimilation product at 10 rn (March 1985-February 1990) and, at the appropriate overlapping times, the European Centre for Medium-Range Weather Forecasts (ECMWF) wind analyses and the Comprehensive Ocean-Atmosphere Data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…The errors are probably due to the closed western boundary and an overly diffuse thermocline in the eastern basin in the model [ Yuan and Rienecker , 2003] that produces overestimated amplitudes of sea level oscillations in the eastern basin (see later). Errors of the wind stress [ Rienecker et al , 1996] can also produce inaccuracies in the simulated circulation, which may ultimately contribute to the model‐altimetry difference through errors of the simulated TIWs. These errors of TIWs, produced by either wind or model errors, are difficult to estimate in the present experiment, except that the error of the closed western boundary can be estimated explicitly through an integration of the Kelvin wave equation and has been shown in the wind‐forced waves (see later).…”
Section: Seasonal Cycle Simulationmentioning
confidence: 99%
“…The errors are probably due to the closed western boundary and an overly diffuse thermocline in the eastern basin in the model [ Yuan and Rienecker , 2003] that produces overestimated amplitudes of sea level oscillations in the eastern basin (see later). Errors of the wind stress [ Rienecker et al , 1996] can also produce inaccuracies in the simulated circulation, which may ultimately contribute to the model‐altimetry difference through errors of the simulated TIWs. These errors of TIWs, produced by either wind or model errors, are difficult to estimate in the present experiment, except that the error of the closed western boundary can be estimated explicitly through an integration of the Kelvin wave equation and has been shown in the wind‐forced waves (see later).…”
Section: Seasonal Cycle Simulationmentioning
confidence: 99%
“…Fortunately, several satellites have observed winds over the ocean during the last two decades, such as the Geo-sat altimeter, the National Aeronautics and Space Administration (NASA) Scatterometer (NSCAT), the Quick Scatterometer (QuikSCAT), the Special Sensor Microwave Imager (SSM/I), European Space Agency Remote Sensing Satellites (ERS-1/2), and water vapor or cloud-derived satellite winds. Comparisons between different observed surface winds or between observed winds and model forecasted/analyzed winds have been studied extensively (Halpern et al 1994;Rienecker et al 1996;Boutin and Etcheto 1996;Meissner et al 2001;Mears et al 2001;Yuan 2004), but no comparisons have been made between SSM/I and QuikSCAT. Boutin and Etcheto (1996) found that SSM/I-retrieved wind speeds are underestimated by more than 1 m s Ϫ1 with respect to ship measurements at high latitudes.…”
Section: Introductionmentioning
confidence: 99%
“…The wind speed observations of SSMI have also been processed using the 2d‐VAR for the entire period of operational SSMI data [ Atlas et al , 1991, 1993, 1996]. The resulting wind fields have proven useful in forcing ocean models in several studies [ Busalacchi et al , 1993; Liu et al , 1996; Atlas et al , 1996; Rienecker et al , 1996] and in assessing the impact of satellite information on surface wind stress estimates [ Ponte and Rosen , 1993]. In this study, we examine the use of 2d‐VAR for NSCAT ambiguity removal.…”
Section: Ambiguity Removal Proceduresmentioning
confidence: 99%